Subunit composition of AMPK trimers present in the cytokinetic apparatus: Implications for drug target identification - Pinter, Katalin (Cell Cycle, 2012)
AMP-activated protein kinase has been shown to be a key regulator of energy homeostasis; it has also been identified as a tumor suppressor and is required for correct cell division and chromosome segregation during mitosis. The enzyme is a heterotrimer, with each subunit having more than one isoform, each encoded by a separate gene (two α, two β and three γ isoforms). In human endothelial cells, the activated kinase subunit of AMPK in the cytokinetic apparatus is α2, the minority α subunit, which co-localizes with β2 and γ2. This is the first demonstration of a trimeric complex of AMPK containing the γ2 regulatory subunit becoming selectively activated and being linked to mitotic processes. We also show that α1 and γ1, the predominant AMPK subunits, are almost exclusively localized in the cytoskeleton, while α2 and γ2 are present in all subcellular fractions, including the nuclei. These data suggest that pharmacological interventions targeted to specific AMPK subunit isoforms have the potential to modify selective functions of AMPK.